2020
DOI: 10.1002/ijfe.2162
|View full text |Cite
|
Sign up to set email alerts
|

A two‐stage Bayesian network model for corporate bankruptcy prediction

Abstract: We develop a Bayesian network (LASSO-BN) model for firm bankruptcy prediction. We select financial ratios via the Least Absolute Shrinkage Selection Operator (LASSO), establish the BN topology, and estimate model parameters.Our empirical results, based on 32,344 US firms from 1961-2018, show that the LASSO-BN model outperforms most alternative methods except the deep neural network. Crucially, the model provides a clear interpretation of its internal functionality by describing the logic of how conditional def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…(2019) found that deep neural networks can predict more accurately than the logistic regression and the naïve Bayes approach. Similar findings emerged from the study by Cao et al. (2020), observing the superior predictive ability of deep neural networks over support vector machines and Bayesian networks.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(2019) found that deep neural networks can predict more accurately than the logistic regression and the naïve Bayes approach. Similar findings emerged from the study by Cao et al. (2020), observing the superior predictive ability of deep neural networks over support vector machines and Bayesian networks.…”
Section: Resultssupporting
confidence: 81%
“…Thus, Alexandropoulos et al (2019) found that deep neural networks can predict more accurately than the logistic regression and the naı €ve Bayes approach. Similar findings emerged from the study by Cao et al (2020), observing the superior predictive ability of deep neural networks over support vector machines and Bayesian networks. Recent developments in deep learning are long-term shortterm neural networks, which simulate a short-term memory by remembering previous expectations.…”
Section: Bankruptcysupporting
confidence: 81%
“…It shows a high ability in bankruptcy prediction with machine learning models to differentiate between bankrupt and non-bankrupt classes. The Receiver Operating Characteristic (ROC) curve is used to calculate the AUC, which measures the efficiency of the applied model to balance between FP and TP rates [44].…”
Section: Performance Evaluation Of the Proposed Modelmentioning
confidence: 99%
“…By identifying early warning signs and potential indicators of financial distress, predictive models play a vital role in informed decision-making and risk management. (Cao et al, 2022) Corporate bankruptcy signifies a state of financial insolvency where a company is unable to meet its debt obligations. This event can have profound effects on employees, shareholders, suppliers, and the broader economy.…”
Section: Introductionmentioning
confidence: 99%